Analisis Dampak Penggunaan Augmented Reality Terhadap Hasil Belajar Kognitif Siswa SMP - Ricka Putri Rizal; Ary Purmadi (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2026)
This study aims to analyze the impact of using Augmented Reality (AR)–based learning media on junior high school students’ cognitive learning outcomes. The study is motivated by the limited use of AR as an instructional medium to support students’ cognitive skills, despite its potential to create more interactive and meaningful learning experiences. A quantitative approach was employed using a quasi-experimental method with a pretest–posttest control group design. The research population consisted of 77 eighth-grade students at SMP Setia Darma Palembang, with two classes selected purposively based on academic ability equivalence, each comprising 30 students. Class VIII A was assigned as the experimental group and received AR-based learning media, while Class VIII B served as the control group and received conventional learning media. The research instrument was a cognitive learning outcomes test in the form of 15 multiple-choice items that had been validated and tested for reliability. Data were analyzed using an independent samples t-test after fulfilling the assumptions of normality and homogeneity. The results indicated a significant difference in cognitive learning outcomes between students who learned using Augmented Reality and those who learned through conventional media (p < 0.05), with an effect size of 0.82, indicating that the use of Augmented Reality had a significant effect on improving junior high school students’ cognitive learning outcomes.